The Influence of Employee Work Effectiveness on the Quality of Public Services at the Tamanan District Office, Kediri City - Putra, Dika Dimas; Hariyati, Alma; Hadi, Marsella Renita (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : The purpose of this research is to analyze the effectiveness of the performance of the government officers of Tamanan District. This research is being conducted in Tamanan District, Kediri City. Design/Methode/Approach : The population of Tamanan District is 5.157 people = 1432 household certificates, whilst the 105 respondents of the research sample is determined through Quota Proportional Random Sampling. Data gathering is being done using questionnaires, whereas data analysis is being done using T-test. Research Finding : Based on the result of the research, the effectiveness of the performance of the government officers of Tamanan District (variable X) has a significant correlation with the quality of public service. Research limitation : There are not too many respondents because it still uses simple research methods, so it can still be researched again using other methods